Metabolic Syndrome Predicts Poor Outcome in Acute Ischemic Stroke Patients After Endovascular Thrombectomy - Chen Z (Dove Medical Press, 2020)
Zhonglun Chen, Mouxiao Su, Zhaokun Li, Hongcai Du, Shanshan Zhang, Mingjun Pu, Yun Zhang Department of Neurology, MianYang Central Hospital, Mianyang, Sichuan 621000, People’s Republic of ChinaCorrespondence: Yun ZhangDepartment of Neurology, Mianyang Central Hospital, 12 Changjia Alley, Mianyang, Sichuan Province 621000, People’s Republic of ChinaTel/ Fax +86 816-2246359Email zhangyun_neuro@126.comBackground and Aims: The metabolic syndrome (MetS) is believed to contribute to a higher probability of developing cardiovascular diseases. This study aimed to investigate whether MetS could predict the prognosis in ischemic stroke patients after endovascular thrombectomy (EVT).Methods: Between January 2016 and September 2019, patients treated with EVT due to large vessel occlusions in anterior circulation were prospectively recruited. MetS was defined using the International Diabetes Federation criteria after admission. The primary outcome was a 3-month poor outcome (modified Rankin scale score of 3– 6). Secondary outcomes included symptomatic intracranial hemorrhage (sICH) and mortality at 3 months. Multivariable logistic regression models were used to assess the relationship between MetS and clinical outcomes.Results: A total of 248 patients were enrolled (mean age, 66.7 years; 37.5% female) and 114 (46.0%) met with the MetS criteria. The median National Institutes of Health Stroke Scale score was 15.0. There were 131 (52.8%) patients achieving the poor outcome at 3 months, among which 26 (10.5%) patients developed sICH. The mortality at 3 months was 19.0% (47/248). In multivariable analysis, MetS was significantly correlated to poor outcome (odds ratio [OR], 2.48; 95% confidence interval [CI], 1.29– 4.78, P = 0.014). The risk for poor outcome was positively associated with the increased number of MetS components (OR 1.78; 95% CI 1.39– 2.35, P = 0.001). No significant findings were found in the association of MetS with sICH and mortality.Conclusion: Our data demonstrated that MetS was associated with poor prognosis in acute ischemic patients treated with EVT.Keywords: metabolic syndrome, ischemic stroke, endovascular thrombectomy, prognosis